In vitro and in vivo inhibition of rabies virus replication by RNA interference - Ono, E. A. D.; Iamamoto, K.; Castilho, J. G.; Carnieli Júnior, P.; Oliveira, R. N.; Achkar, S. M.; Carrieri, M. L.; Kotait, I.; Brandão, P. E. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is a zoonotic disease that affects all mammals and leads to more than55,000 human deaths every year3, caused by rabies virus (RABV) (Mononegavirales: Rhabdoviridae: Lyssavirus). The search for antivirals against rabies isone of the frontiers in the field but, despite a protocol (the Milwaukee Protocol)based on ketamin, ribavirin, midazolam and amantad in was successful after the treatment of a human patient,4 it was shown as not reproducible. RNA interference is an alternative as antiviral technology against RABV already shown as effective in vitro in cell cultures 1,2, but no reports on its in vivouse exist hitherto. The aim of this study was to assess the decrease in the titerof rabies virus both in vitro and in vivo using short-interfering RNAs. To thisend, three siRNAs were used with antisense strands complementary to rabiesvirus nucleoprotein (N) mRNA. BHK-21 cells monolayers were infected with1,000 to 0.1 TCID50 of PV and after 2 hours the cells were transfected witheach of tree RNAs in separate using Lipofectamine-2000™. All three siRNAs reduced the titer of PV strain in a least 0.72 logTCID50/ml and no cytotoxiceffect was observed in the monolayers treated with Lipofectamine-2000™.Swiss albino mice infected with 10.000 to 1LD of PV strain by the intracerebral route were also transfected after two hours of infection with a pool 3 siRNAs with Lipofectamine-2000™ by the intracerebral route, resulting in a survival rate of 30% in mice inoculated with 100 LD50, while the same dose led to100% mortality in untreated animals. Lipofectamine-2000™ showed no toxiceffect in control mice. These results suggest that intracerebral administration of siRNAs might be an effective antiviral strategy for rabies.